EVOLUTION AND APPLICATIONS OF RADIOPHARMACEUTICALS IN NUCLEAR DENTISTRY: A COMPREHENSIVE OVERVIEW - Alina Stefanache; Cozmin Mihai; Ionut Iulian Lungu; Gabriela Calin; Cristian Mihalache; Deleu Grigorii; Budirinca Maria Alexandra; Catalina Girbia; Oana Cucoveica; Carmen Stadoleanu; Norin Forna; Carmen Grierosu (Romanian Society of Oral Rehabilitation, 2024)
Aim of the Study: Radiopharmaceuticals in nuclear dentistry represent a dynamic field, contributing significantly to the evolution of restorative dentistry. This comprehensive overview focuses on the advancements and applications of these radiopharmaceuticals, aiming to elucidate their role in modern dental practices. Nuclear Medicine (NM) imaging has emerged as a crucial tool for early disease diagnosis in recent decades, complementing conventional imaging modalities in the head and neck region. While conventional techniques like radiographs, Cone Beam Computed Tomography (CBCT), and Computed Tomography (CT) are commonly used, NM is specifically employed for certain oral and maxillofacial pathologies. Utilizing radioactive isotopes emitting gamma (γ) rays, NM provides detailed insights into tissue metabolism and physiological processes, offering precise functional and biochemical information for accurate diagnosis. Despite not being a routine practice in dentistry, dental professionals should be acquainted with NM's various applications in the oral and maxillofacial region, as highlighted in this review. Material and Methods: Extensive research was conducted through systematic searches on electronic databases, including PubMed, Google Scholar, and Web of Science. The search targeted articles released from April onwards, with an exclusive focus on English-language publications. A comprehensive set of keywords, such as "radiopharmaceuticals in nuclear dentistry," "evolution," "applications," "advancements," "biocompatibility," "imaging techniques," "clinical outcomes," and "dental radiology," were employed to gather relevant information. Results: The exploration of radiopharmaceuticals in nuclear dentistry reveals their transformative potential as innovative tools in contemporary dental care. A comprehensive analysis of their evolution, applications, and advancements underscores their diverse benefits for both dental practitioners and patients. Conclusions: Continued research and development efforts are anticipated to further solidify the pivotal role of radiopharmaceuticals in nuclear dentistry. With their expanding applications and ongoing enhancements, these agents are poised to remain integral components in advancing dental care, offering substantial benefits to both practitioners and patients within the realm of dental radiology and treatments. n conclusion, Nuclear Medicine imaging emerges as a powerful adjunct in dentistry, offering unique insights into functional and biochemical aspects for precise oral and maxillofacial diagnoses. While not a daily practice, awareness of its applications is crucial for dental professionals to enhance their diagnostic capabilities and contribute to comprehensive patient care.